Delirium in Elderly Patients (Springer International Publishing, 2018)
This book provides a comprehensive, scholarly, and practical account of delirium that will be of value for all doctors and nurses involved in the care of the elderly. It not only offers a state of the art update on delirium, covering its history, epidemiology, pathophysiology, assessment, diagnosis, causes, prevention, and management, but also presents evidence-based and practical information relevant to daily clinical routine. Owing to the complex multifactorial causes of delirium, different aspects of delirium in the elderly are discussed from a variety of perspectives. The book closes by presenting a series of case vignettes, delirium assessment tools and screening scales, and a list of those drugs highly associated with delirium. Delirium is a cognitive disorder characterized by deficits in attention, arousal, consciousness, memory, orientation, perception, speech, and language. It is a common and serious problem among older persons at every healthcare interface. Although it occurs in 10-60% of the older hospitalized population, delirium remains a relatively misunderstood and misdiagnosed condition. This book will be of interest to professionals working in geriatrics, geriatric psychiatry, general psychiatry, or neurology, internists, intensive care unit specialists, and all who care for the elderly in hospitals or the community.